A Diagnosis of Tourist Forms Popularized by Travel Bloggers in Poland - Jakubowska, Magdalena (Studia Oeconomica Posnaniensia, 2018)
The aim of the paper is to try to determine the forms of tourism popularized by travel bloggers in Poland. The research hypothesis assumed that there are forms of tourism popularized by the majority of online bloggers. The first part of the study is a literature review, including the results of research on Internet opinion leaders in relation to tourism, such as bloggers and forms of tourism, taking into account different criteria. The second part of the paper contains the concept and research results, carried out by an observation method. The results of the analysis made it possible to determine the forms of tourism promoted by Polish travel bloggers in Poland. The hypothesis was confirmed.